Pengaruh Model Pembelajaran Problem Based Learning Berbantuan LKPD Interaktif terhadap Hasil Belajar IPAS Siswa Kelas III SDN 15 Cakranegara - Maya Ardinita; Nurhasanah; I Putu Herry Widhi Andhika (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The understanding of science material of third grade students of SDN 15 Cakranegara is still low because learning tends to be passive, teacher-centered, and the use of LKPD is limited to printed form. This study aims to determine the effect of the application of the Problem Based Learning (PBL) model assisted by interactive LKPD on the science learning outcomes of third grade students of SDN 15 Cakranegara. The study used a quantitative approach with a Quasi Experimental design of the Nonequivalent Control Group Design type. The research sample was all third grade students, with class III A as the experimental group and class III B as the control group. Data were collected through learning outcome tests and observations, then analyzed using the Kolmogorov-Smirnov normality prerequisite test and Levene's homogeneity test, as well as hypothesis testing with the Independent Sample t-test. The results of the study obtained from the hypothesis test are sig. (2-tailed) <0.05, namely 0.000 <0.05 and the tvalue of 6.036> ttabel 2.004, so Ha is accepted and H0 is rejected. These findings confirm that the implementation of PBL assisted by interactive worksheets has an impact on students' science learning outcomes. The effect size test yielded a Cohen's d value of 1.59, categorized as a large effect, proving that the influence is strong and practically meaningful.